LABORATORY CHANGES IN VITAMIN D IN HELMINTHIC DISEASES IN CHILDREN (Proceedings of Scientific Conference on Multidisciplinary Studies, 2024)
In Uzbekistan, the most common helminthiases are: enterobiasis, ascariasis, trematodosis. The incidence of enterobiasis in the country is 1100 cases per 100 thousand of the population. Among the patients, 90% are children, mainly aged 1 to 3 years. The incidence of geminolepiasis is 100 cases per 100 thousand of the population. In the Aral Sea region, intestinal helminthiases occupy a leading place in the structure of the disease, and enterobiasis and geminolepiasis are common among them, accounting for more than 40% of all identified helminthiases.Vitamin D has a modulating effect on the immune system and in case of its deficiency the immune system may be affected. It has been stated that the risk of developing bacterial, viral and fungal infections as well as parasitic infections may increase in immunosuppressive conditions.